2018
DOI: 10.1038/s41598-018-33642-1
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic 5-lncRNA Expression Signature for Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a common malignant cancer that accounts for 5–10% of all cancers. This study aimed to identify essential genes associated with the prognosis of HNSCC and construct a powerful prognostic model for the risk assessment of HNSCC. RNAseq expression profile data for the patients with HNSCC were obtained from the TCGA database (GEO). A total of 500 samples with full clinical following-up were randomly divided into a training set and a validation set. The training set w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Squamous cell carcinoma of the head and neck JHU011, CAL33 and CAL27 cell lines were kindly provided by Dr Joseph Califano (University of California, San Diego, USA). Tu686 cell line was kindly provided by Dr Zhuo G. Chen (Emory University Winship Cancer Institute, USA) . Tca8113 cell line was obtained from The Cell Bank of Type Culture Collection of Chinese Academy of Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…Squamous cell carcinoma of the head and neck JHU011, CAL33 and CAL27 cell lines were kindly provided by Dr Joseph Califano (University of California, San Diego, USA). Tu686 cell line was kindly provided by Dr Zhuo G. Chen (Emory University Winship Cancer Institute, USA) . Tca8113 cell line was obtained from The Cell Bank of Type Culture Collection of Chinese Academy of Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…A large portion of the studies regarded mRNA signatures (33/61) , while a minor portion of the studies considered miRNA signatures (11/61) [52][53][54][55][56][57][58][59][60][61][62] and other non-coding RNA signatures (13/61) [63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Only 4/61 [77][78][79][80] studies identified signatures by a high-throughput omics analysis of methylated DNA.…”
Section: Analysis Of Recent Epigenomics and Transcriptomics Datamentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) refer to the type of noncoding RNA that is derived from genome-encoded transcripts with lengths longer than 200 RNA nucleotides (3). Recent studies suggest it may be directly involved in the regulation of development of tumor cells (4)(5)(6). LncRNAs are involved in the regulatory network of thyroid carcinomas.…”
Section: Introductionmentioning
confidence: 99%